Publisher's Note on 39 papers regarding Digital Object Identifiers. (Genetics, 2026)
This Publisher's Note addresses changes to the Digital Object Identifiers (DOIs) for all papers published in Volume 166, Issue 2 (February 2004) of the journal Genetics. When Oxford University Press began publishing the journal on behalf of the Genetics Society of America in 2021, it was discovered that the original DOIs had not been registered with CrossRef, leading to a change in the DOI prefix from 10.1534 to 10.1093. The note clarifies this update and apologizes for any confusion it may have caused.